Improving Innovative Behavior through Strengthening Transformational Leadership, Self-Efficacy, Knowledge Sharing, and Creativity (Empirical Study Using SEM PLS and SITOREM Analysis on Private Vocational School Teachers in South Jakarta) - Rosalina Dewi Heryani; Rita Retnowati; Rais Hidayat (Journal of World Science, 2025)
The research aims to identify optimal strategies to enhance innovative behavior by strengthening transformational leadership, self-efficacy, knowledge sharing, and creativity. Utilizing a quantitative approach with path analysis via SEM PLS and SITOREM, data was collected through questionnaires from 179 permanent teachers at 16 private vocational schools in South Jakarta. The findings revealed that transformational leadership has a direct positive but insignificant impact on innovative behavior, while self-efficacy also shows a direct negative and insignificant influence. Knowledge sharing and creativity demonstrated direct positive but insignificant effects on innovative behavior. However, transformational leadership and self-efficacy positively and significantly impact knowledge sharing and creativity. Indirect influences of transformational leadership and self-efficacy on innovative behavior through knowledge sharing and creativity were found to be insignificant. The study suggests implementing improvement strategies by enhancing weak indicators and maintaining strong ones, prioritizing the areas needing attention to optimize innovative behavior.